2012
DOI: 10.1051/0004-6361/201218952
|View full text |Cite
|
Sign up to set email alerts
|

GOODS-Herschel: ultra-deepXMM-Newtonobservations reveal AGN/star-formation connection

Abstract: Models of galaxy evolution assume some connection between the AGN and star formation activity in galaxies. We use the multi-wavelength information of the CDFS to assess this issue. We select the AGNs from the 3 Ms XMM-Newton survey and measure the star-formation rates of their hosts using data that probe rest-frame wavelengths longward of 20 μm, predominantly from deep 100 μm and 160 μm Herschel observations, but also from Spitzer-MIPS-70 μm. Star-formation rates are obtained from spectral energy distribution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
129
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 168 publications
(215 reference statements)
24
129
5
Order By: Relevance
“…They suggest that the sSFRs of AGN are consistent with those of star-forming galaxies, with possible exceptions the luminous AGN (e.g. Rovilos et al 2012;Treister et al 2012). Most of these X-ray works investigate the mean SFRs of AGNs that are less luminous than those studied here, and should also include a high fraction of narrow-emission line AGN.…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 65%
See 1 more Smart Citation
“…They suggest that the sSFRs of AGN are consistent with those of star-forming galaxies, with possible exceptions the luminous AGN (e.g. Rovilos et al 2012;Treister et al 2012). Most of these X-ray works investigate the mean SFRs of AGNs that are less luminous than those studied here, and should also include a high fraction of narrow-emission line AGN.…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 65%
“…Shao et al 2010;Harrison et al 2012;Mullaney et al 2012b;Rovilos et al 2012;Santini et al 2012;Rosario et al 2013). They suggest that the sSFRs of AGN are consistent with those of star-forming galaxies, with possible exceptions the luminous AGN (e.g.…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 99%
“…There is observational evidence that some co-evolution between the AGN and the host galaxy exists (e.g., the M-σ relation, Ferrarese & Merritt 2000), and recent observations link host star formation rates to their AGN for different luminosities and redshifts (see Shao et al 2010;Mullaney et al 2012;Rovilos et al 2012;Rosario et al 2012, but also Page et al 2012). In Fig.…”
Section: The Extended Emissionmentioning
confidence: 88%
“…Already, observations from Herschel have been used to great effect to investigate the relationship between various types of AGN and their starbursting host galaxies. In galaxies with X-ray-selected AGN, numerous studies have found correlations between the strength of the starburst in galaxies, as determined by Herschel, and the strength of the AGN they host (Shao et al 2010;Harrison et al 2012b;Rovilos et al 2012;Santini et al 2012; though for an alternative viewpoint see Page et al 2012). The host galaxies of radio-and IR-selected AGN have also been the subjects of investigation with Herschel (e.g., Hardcastle et al 2012;Del Moro et al 2013), though the connection between these AGNs and their host galaxies is less clear than in the case of X-ray-selected AGN.…”
Section: Introductionmentioning
confidence: 99%